Dispersal by generalist frugivores affects management of an invasive plant. (21st July 2016) - Ramaswami, Geetha; Kaushik, Monica; Prasad, Soumya; Sukumar, Raman; Westcott, David
Abstract: In the past century, our understanding of the processes driving plant invasion and its consequences for natural and anthropogenic systems has increased considerably. However, the management of invasive plants remains a challenge despite ever more resources being allocated to their removal. Often invasive plants targeted for 'eradication' are well‐established, have multiple modes of reproduction, long‐term seed banks, and strong associations with native and non‐native mutualists that ensure dispersal and facilitate spread. The pantropical weed, Lantana camara (Lantana), is one of the most invasive woody plants globally. We illustrate that, for Lantana, eradication is an unrealistic management goal given the short‐term removal approaches, irrespective of the effectiveness of removal methods. We assessed the role of dispersal by avian frugivores in the recolonization of managed areas by Lantana in the seasonally dry, tropical forests of northern and southern India. We estimated the distribution of Lantana, its dispersal potential and the proximity between managed areas and source populations. We found that Lantana was dispersed by many generalist frugivorous birds and that most managed areas were well within the median dispersal distance from source plants facilitating rapid recolonization of managed areas. We conclude that given the difficulty of eradicating long‐established invasive plants, management practices should entail long‐term monitoring and control in priority areas for as long as Lantana occurs in the landscape.